Unilateral Warthin's tumour in a patient of Afro-Caribbean descent. (2nd June 2014) - Quintyne, KI; Wallis, F; Healy, V; Shine, N
Abstract : Warthin's tumours are the second most common benign tumours of the parotid gland. The authors report the case of a 40-year-old man of Afro-Caribbean decent who presented with a painless mass at the angle of the right mandible. It was an incidental finding while shaving and was not associated with any symptoms. Arrangements were made for him to undergo an ear, nose and throat (ENT) evaluation. Axial contrast-enhanced CT of head and neck region revealed a well-defined cystic lesion. Fine-needle aspiration cytology was inconclusive. Right superficial partial parotidectomy was performed to remove the lesion. Histological examination confirmed a diagnosis of a Warthin's tumour.